Aquatic Macro-invertebrates as Bio-indicators: An Approach for Wetland Water Quality Assessment of Rampur Ghol, Chitwan, Nepal - Gautam, Birendra; Maskey, Rejina; Sapkota, Ramesh Prasad; Dangol, Dharma Raj (Journal of Institute of Science and Technology, 2015)
The present research was conducted to study seasonal limnological parameters and record composition pattern of aquatic macro-invertebrates of the Rampur Ghol. GRS-BIOS/ASPT index was used to calculate the water quality class, Shannon Weiner diversity index (H’) and Piélou evenness index (e) were used to determine taxa richness of the macroinvertebrates. Altogether 281 individuals of 14 families and 313 individuals of 18 families were recorded in dry season and rainy season, respectively. Similarly, diversity index and evenness index values were recorded 0.98 and 0.85 in dry season; 1.075 and 0.86 in rainy season. On the basis of different aquatic macro-invertebrates, GRS-BIOS/ASPT Index value of four sampling sites fall in class II (moderately polluted), four sampling sites belong to water quality class IIIII (critically polluted) and remaining two sampling sites belong to water quality class III (heavily polluted). Similarly, in rainy season seven sites fall in water quality class II (moderately polluted) and three sampling sites belong to water quality class II-III (critically polluted). Journal of Institute of Science and Technology, 2014, 19(2): 58-64